INSULIN INITIATION IN T2DM: OUTCOMES ON GLYCAEMIC CONTROL, BODY WEIGHT, AND HYPOGLYCEMIA RISK - Ng, Ooi Chuan; Ng, Jo-An (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION The prevalence of diabetes in Malaysia is rising due to urbanization and socioeconomic changes. Despite evidence supporting good glycaemic control, maintaining optimal control remains challenging, with mean HbA1c levels ranging from 7.9% to 8.1%. Progressive beta-cell failure leads to secondary OAD (oral antidiabetic drugs) failure, necessitating insulin therapy. This study evaluates the effect of a simple insulin therapy protocol on glycaemic control in T2DM patients with secondary OAD failure. METHODOLOGY A prospective study was conducted in outpatient clinics at Hospital Kuala Lumpur and Hospital Serdang. Patients with T2DM and secondary OAD failure (HbA1c >9%, fasting plasma glucose ≥9 mmol/L) were recruited. The intervention group received bedtime NPH insulin (Insulatard® Penfill®) with dose titration, while the control group continued OAD therapy. HbA1c, fasting blood glucose (FBG), insulin dosage, and hypoglycaemia events were assessed at baseline, Month 3, and Month 6. RESULT Forty-five patients (mean age 55.1 ± 9.3 years, diabetes duration 9.7 ± 8.1 years) were included. At Month 6, HbA1c in the intervention group was significantly reduced by 1.28%, with 26.7% achieving HbA1c <8%. Mean FBG decreased by 3.6 mmol/L. Insulin dose stabilized at 0.33 ± 0.13 IU/kg/day. Mean body weight change was +1.78 kg in the intervention group. One patient experienced mild hypoglycaemia. CONCLUSION A patient-guided insulin titration protocol improved glycaemic control in T2DM patients with secondary OAD failure, supporting its feasibility in local primary care settings.